Private equity and venture capital: investment fund structures in the Czech Republic - Marek Zinecker (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2011)
A working private equity and venture capital market (PE/VC market) stimulates the business environment in a positive manner and impacts the level of economic growth of national economies. A study of the Austrian Private Equity and Venture Capital Organisation/AVCO (2004, p. 6) defines prerequisites for a correct operation of the PE/VC market. It views the legislative provision for suitable legal fund structures for PE/VC investments and their tax treatment as a key factor. In its publication, Private Equity & Venture Capital in the Czech Republic (2010, p. 14), the Czech Venture Capital Association/CVCA stresses that legal barriers are an important reason behind the limited scope of resources available to domestic PE/VC funds. Legal barriers prevent the establishment of a standard PE/VC fund in the territory of the Czech Republic, which fact in turn has a negative impact on the level of development of the domestic PE/VC market (fundraising, investment volumes, establishment of the infrastructure required for the operation of PE/VC funds). The purpose of this article is, based on an analysis of the relevant information sources, to assess how the current Czech legislation regulates the legal fund structures for PE/VC investments and their tax treatment. Proposals for a potential improvement of the situation are based on a comparison of the legislative framework applicable in the Czech Republic and the requirements defined by the European Venture Capital Association/EVCA, as well as the AVCO study (2004, 2006).